2013
DOI: 10.1080/15374416.2012.719460
|View full text |Cite
|
Sign up to set email alerts
|

Throwing Caution to the Wind: Callous-Unemotional Traits and Risk Taking in Adolescents

Abstract: Citation for published item:gentifnti @n¡ ee wu£ nozAD vFgF nd wodekiD uFvF @PHIQA 9hrowing ution to the wind X llousEunemotionl trits nd riskEtking in dolesentsF9D tournl of linil hild nd dolesent psyhologyFD RP @IAF ppF IHTEIIWF Further information on publisher's website:his is n eletroni version of n rtile pulished in gentifnti @n¡ ee wu£ nozAD vFgF nd wodekiD uFvF @PHIQA 9hrowing ution to the wind X llousEunemotionl trits nd riskEtking in dolesentsF9D tournl of linil hild nd dolesent psyhologyFD RP @IAF pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 73 publications
4
29
1
Order By: Relevance
“…Likewise, Marini and Stickle [136] found an inverse correlation between the CU traits of incarcerated youth reward responsivity on a laboratory task. Centifanti and Modecki [137] reported a similar finding among a large sample of high-school students.…”
Section: Development Of Psychopathic Violencesupporting
confidence: 58%
“…Likewise, Marini and Stickle [136] found an inverse correlation between the CU traits of incarcerated youth reward responsivity on a laboratory task. Centifanti and Modecki [137] reported a similar finding among a large sample of high-school students.…”
Section: Development Of Psychopathic Violencesupporting
confidence: 58%
“…After controlling for sensation seeking and impulsivity, CU traits were associated with less risk taking following reward (i.e., the number of button presses following a non-popped balloon; Marini and Stickle 2010). Similarly, Centifanti and Modecki (2013) examined the association between CU traits, risk taking and peer influence in a large community sample and found no association between CU traits and overall risk taking after accounting for gender and peer influence. Moreover, CU traits were associated with less risk taking following reward.…”
Section: Behavioral Researchmentioning
confidence: 99%
“…The average number of pumps across unexploded balloons estimates risk taking behavior (Lejuez et al, 2007). Although the BART is positively correlated with real life risky health behaviors (e.g., substance use) (Lejuez et al, 2007; Lejuez, Aklin, Zvolensky, & Pedulla, 2003; MacPherson, Magidson, Reynolds, Kahler, & Lejuez, 2010), few studies have tested the predictive validity of the BART with respect to youth conduct problems (Centifanti & Modecki, 2013; Crowley, Raymond, Mikulich-Gilbertson, Thompson, & Lejuez, 2006). Humphreys and Lee (2011) reported that children with comorbid ADHD and ODD exhibited more risk taking on the BART relative youth with ADHD only and non-disordered comparison youth.…”
mentioning
confidence: 99%